Stroke and mortality rates after valve-in-valve TAVR and comparison with data from redo SAVR. (25th November 2020) - Macherey, S; Meertens, M; Eichel, S; Schipper, J; Mauri, V; Frerker, C; Adam, M; Kuhn, E; Wahlers, T; Lee, S; Baldus, S; Schmidt, T
Abstract: Background and purpose: Early registry data described a potentially increased risk for cerebrovascular events and mortality in patients undergoing transcatheter aortic valve replacement (TAVR) as valve-in-valve (viv) procedures. Further data of small patient cohorts described divergent results for cerebrovascular events and mortality in patients undergoing TAVR as viv procedures for failed surgical bioprotheses in comparison with patients on redo surgical aortic valve replacement (SAVR). We performed a meta-analysis of stroke rates and mortality for viv TAVR procedures basing on the current literature. Methods: We included all case series (≥10 patients), case-control studies and randomized controlled trials comparing viv TAVR and redo SAVR procedures with respect to cerebrovascular events and mortality rates. Additionally, we included all case series and registries with patients undergoing viv TAVR. After a structured literature research, 17 studies were eligible. For statistical analysis risk ratios and confidence intervals using Mantel-Haenszel test and the I-statistic to quantify possible heterogeneity were calculated. A P-value <0.05 was defined as statistical significant difference. Results: Eleven case series and registries reporting on stroke and mortality in 8, 509 patients undergoing viv TAVR were eligible for analysis. The quantitative analysis of non-comparative studies showed a calculated 30-day stroke rate of 2.2% and 30-day mortality rate of 4.2% after viv TAVR. Data on the 1-year rates were sporadically reported, therefore meta analysis was not appropriately feasible. Six studies reporting on 498 participants undergoing viv TAVR (N=254) and redo SAVR (N=244) were eligible. The median age ranged from 72.3 to 80.2 years for viv TAVR and from 66.2 to 78.8 years for redo SAVR patients. The STS score was 7.2–7.4% (viv TAVR) and 5.8–7.7% (redo SAVR), respectively. A total of 3/226 participants treated with viv TAVR and 4/214 patients undergoing redo SAVR experienced a stroke during the first 30 postoperative days (N=4 trials, RR 0.86, 95% CI 0.20 to 3.59, p=0.83, I 2 = 0%). None of the studies reported sufficient data on the 1-year stroke incidence. The 30-day mortality was 4.3% for viv TAVR and 4.5% for redo SAVR patients. This difference was not significantly different (N=6 trials, RR 0.90, 95% CI 0.40 to 2.05, p=0.80, I 2 = 0%). The 1-year mortality rates were 13.3% and 13.6%, respectively (N=2 trials, RR 0.98, 95% CI 0.49 to 1.94, p=0.94, I 2 = 0%). Conclusion: In the current literature favorable stroke and mortality rates at 30 days for patients undergoing viv TAVR are documented. Similar stroke and mortality rates comparing viv TAVR and redo SAVR patients at 30 days were found as well as similar 1-year mortality. A selection bias for the viv TAVR and redo SAVR patients may exist, but cannot be dissolved with this registry analysis, only showing a trend of younger and lower risk patients receiving a redo SAVR procedure. Funding Acknowledgement: Type of funding source: None